2021
DOI: 10.1152/japplphysiol.00502.2020
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contributions of skin and core temperatures to flow-mediated dilation of the brachial artery following passive heating

Abstract: We measured acute vascular responses to heat stress to examine the hypothesis that macrovascular endothelial-dependent dilation is improved in a shear-dependent manner, which is further modified by skin temperature. Twelve healthy males performed whole-body heating (+1.5°C esophageal temperature), bilateral forearm heating (~38°C skin temperature), and a time-matched (~60 min) control condition on separate days in counterbalanced order. Bilateral assessments of blood flow and brachial artery flow-mediated dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 66 publications
4
22
0
Order By: Relevance
“…The increase in blood flow to the heated leg region occurred in the face of a maintained diameter in all examined conduit arteries, including those of the control leg and/or control leg segment where blood velocity and flow did not change. The present findings agree with studies reporting no changes in conduit artery diameter during limb heating (Chiesa et al, 2016;Coombs et al, 2019Coombs et al, , 2021Pearson et al, 2011;Teixeira et al, 2017), but are at odds with studies showing decreases in POA diameter (Thomas et al, 2017). The unchanged conduit artery diameter, together with the general increases in local vascular conductance with whole leg and segmental leg hyperthermia, suggest that vasodilatation might have instead occurred in the downstream small arteries and resistance arterioles, and/or alternatively thermosensitive physical and chemical mechanisms governing blood's rheological properties and kinetic energy permitted the increase in microvascular blood velocity and flow.…”
Section: Tissue Perfusion Regulation During Local Hyperthermiasupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in blood flow to the heated leg region occurred in the face of a maintained diameter in all examined conduit arteries, including those of the control leg and/or control leg segment where blood velocity and flow did not change. The present findings agree with studies reporting no changes in conduit artery diameter during limb heating (Chiesa et al, 2016;Coombs et al, 2019Coombs et al, , 2021Pearson et al, 2011;Teixeira et al, 2017), but are at odds with studies showing decreases in POA diameter (Thomas et al, 2017). The unchanged conduit artery diameter, together with the general increases in local vascular conductance with whole leg and segmental leg hyperthermia, suggest that vasodilatation might have instead occurred in the downstream small arteries and resistance arterioles, and/or alternatively thermosensitive physical and chemical mechanisms governing blood's rheological properties and kinetic energy permitted the increase in microvascular blood velocity and flow.…”
Section: Tissue Perfusion Regulation During Local Hyperthermiasupporting
confidence: 93%
“…In local limb hyperthermic conditions where perfusion pressure remains stable, an increase in vascular conductance—and thus an increase in arterial diameter and/or blood velocity—could explain the hyperthermia‐induced hyperemia. Nevertheless, whether local hyperthermia increases conduit artery diameter remains equivocal, with studies reporting increases (Kalsi et al, 2017 ), decreases (Thomas et al, 2017 ), or no changes in arterial diameter (Chiesa et al, 2016 ; Coombs et al, 2021 ; Pearson et al, 2011 ; Teixeira et al, 2017 ). Moreover, hyperthermia may directly act on the conduit artery supplying blood to the heated region by increasing arterial stiffness/decreasing arterial distensibility rather than altering diameter, as seen during incremental exercise (Pomella et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…During-assessment, it is important to control environmental conditions, including ambient noise and temperature. Ambient noise may raise arousal, whilst core temperature and skin temperature have both been reported to affect vascular function (53). Fluid replacement should also be considered.…”
Section: Internal Validitymentioning
confidence: 99%
“…Owing to protocol variability, studies examining the acute impact of passive heat stress yield mixed results. With acute heating, macrovascular endothelial function has been shown to increase in some (16)(17)(18) but not all instances (19)(20)(21) in the brachial artery (BA); whereas the superficial femoral artery (SFA) appears resistant to change (13,20,22). In contrast, Cheng et al Acute lower limb heating and vascular function microvascular function has been shown to increase in some (13,17) but not all instances (19)(20)(21) in both the BA and SFA.…”
Section: Introductionmentioning
confidence: 99%
“…With acute heating, macrovascular endothelial function has been shown to increase in some (16)(17)(18) but not all instances (19)(20)(21) in the brachial artery (BA); whereas the superficial femoral artery (SFA) appears resistant to change (13,20,22). In contrast, Cheng et al Acute lower limb heating and vascular function microvascular function has been shown to increase in some (13,17) but not all instances (19)(20)(21) in both the BA and SFA. Arterial stiffness has also been shown to decrease when examined in the upper limb (23) or whole-body (12), but not in the central or lower limb segments (23).…”
Section: Introductionmentioning
confidence: 99%